1985
DOI: 10.1002/cne.902350103
|View full text |Cite
|
Sign up to set email alerts
|

Floccular efferents in the rhesus macaque as revealed by autoradiography and horseradish peroxidase

Abstract: To fulfill its putative role in short- and long-term modification of the vestibulo-ocular reflex, the flocculus of the cerebellum must send efferents to brainstem nuclei involved in the control of eye movements. In order to reveal the sites of these interactions, we determined the projections of the flocculus by autoradiography and orthograde transport of horseradish peroxidase in five rhesus macaques. Anterogradely labeled axons collected at the base of the injected folia and coursed caudally and medially bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(69 citation statements)
references
References 42 publications
7
62
0
Order By: Relevance
“…Namely, our previous report on vertical Purkinje cells (Blazquez et al 2003) (Blazquez et al 2000;Langer et al 1985;Partsalis et al 1995b). To calculate G FTN_vestib , we utilize a particular property found in the Purkinje cell population and graphically described in Fig.…”
Section: Model and Estimation Of Signal Transmission Efficacies In Otmentioning
confidence: 93%
See 1 more Smart Citation
“…Namely, our previous report on vertical Purkinje cells (Blazquez et al 2003) (Blazquez et al 2000;Langer et al 1985;Partsalis et al 1995b). To calculate G FTN_vestib , we utilize a particular property found in the Purkinje cell population and graphically described in Fig.…”
Section: Model and Estimation Of Signal Transmission Efficacies In Otmentioning
confidence: 93%
“…The only known source of eye velocity to Y neurons arrives from the flocculus (Partsalis et al 1995b;Rambold et al 2002). The head signal, however, arrives to Y neurons via two pathways: the flocculus, which sends an upward head velocity signal (inhibitory synapses convert the downward head velocity of Purkinje cells to upward head velocity) (Langer et al 1985;Partsalis et al 1995b), and interneurons with either up or down head-velocity signal are located in the superior vestibular nucleus (SVN) (Blazquez et al 2000;Sato and Kawasaki 1987). In the normal gain or naïve animal, Y neuron head-velocity sensitivity arrives almost exclusively from the flocculus because inputs from up-head and down-head velocity interneurons in the superior vestibular nucleus cancel each other at the level of the dorsal Y group, as suggested by pharmacological inactivation of the cerebellar flocculus (Partsalis et al 1995b).…”
Section: Introductionmentioning
confidence: 99%
“…That study found that the region at the border of PH and VMN, the site of our dense patch of calbindin-labeled fibers, was free of calbindin-labeled fibers in those animals. Several studies suggest the most likely source of cerebellar projections to the regions of dense calbindin fiber label is the flocculus (Sato et al 1982;Langer et al 1985a;Shojaku et al 1987;Umetani 1992;De Zeeuw et al 1994;Tan et al 1995). The calbindin-dense patches thus define input compartments.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…A number of parallel and interconnected pathways are involved in initiating and maintaining smooth-pursuit eye movements (for review, see Keller and Heinen 1991); however, particular importance has been assigned to the cortico-ponto-cerebellar pathway arising from the medial superior temporal sulcus (MST) of the extrastriate cortex. This pathway accesses the brain stem circuitry via inhibitory projections from the ipsilateral cerebellar flocculus and ventral paraflocculus, herein referred to as the floccular lobe (Balaban et al 1981;Dow 1937;Gerrits and Voogd 1989;Langer et al 1985). Under more natural conditions (i.e., when the head is not restrained), humans and primates use coordinated movements of the head as well as the eyes, referred to as gaze pursuit, to align their axis of gaze (gaze ϭ eye-in-head position ϩ headin-space position) with a moving target.…”
Section: Introductionmentioning
confidence: 99%